ITALIAN DOUBLE ENTRY IN EARLY ENGLAND. - Littleton, A. C. (The Accounting Review, 1926)
Abstract This article focuses on the practice of Italian double entry system of accounting in early England as of June 1926. It appears that the early ledger entries were fairly complete sentences expressing complete ideas. They were in fact memoranda of what the writer wanted to avoid forgetting and probably were cast into the forms of expression of ordinary speech. What we find written in the old books gives us therefore some idea of how 15th century merchants thought their transactions through for recording purposes. The social background, so different from the independent life of the individual in Italy, would be expected to produce a very different kind of "recording-need" and a very different attitude toward the ends to be accomplished by the records. Feudalism produced an atmosphere of agency and stewardship rather than ownership and proprietors hip, such as was engendered in the more commercial Italy. None but the King was absolute sovereign over his property with full, free, and untrammeled power to dispose of it without consulting the plans or will of another. The nobles held their lands under the King's pleasure and the noble's peasant tenants held such land as they used solely tinder their master's pleasure. English "business" in the 13th and 14th centuries was confined to small artisans and peddlers-nothing to call up any sort of record-keeping. The largest activity was the maintenance of the manor house and its self-sufficing community.